61 Comparison of Clinical Outcomes of Robotic Versus Open Pancreaticoduodenectomy Using a New 'Therapeutic Index' Tool for Quality Assessment of Surgery: A Systematic Review and Meta-Regression Analysis. (19th August 2022) - Mantzavinou, Artemis; Uppara, Mallikarjuna; Chan, Jeremy; Patel, Bijendra
Abstract: Aim: Pancreaticoduodenectomy (PD) is a challenging procedure with peri-operative complications. Robotic surgery offers improved dexterity, visibility, and accessibility. Recently, many centres have reported improved clinical outcomes for robotic PD. We reviewed the safety and efficacy of robotic PD in comparison to open PD using 'Therapeutic Index' (TI). Method: A systematic review of the literature was conducted in various databases. Articles published between January 2010 and March 2021 reporting totally-robotic and open PD were included, according to PRISMA guidelines. The Cochrane tool was used for risk of bias assessment. We compared 30-day mortality rates (MR30 ), lymphadenectomy rates (LR), R0 resection rates (R0 RR) and therapeutic index (TI). STATA 16.1 was used for statistical analysis. Results: The four studies that met inclusion criteria included 5090 PDs, out of which 617 were totally robotic (RPD) and 4473 were open (OPD). Variance ratio tests demonstrated a) Higher TI for RPD versus OPD (1807.42 vs 1723.37, p=0.86), b) Significantly smaller MR30 (2.50 vs 19.00, p=0.0004), c) Significantly lower R0 RR (130.50 vs 939.25, p=0.00) and d) No significant difference in LR between RPD and OPD (35.63 vs 38.25, p=0.81). Meta-regression analysis showed a significantly higher TI coefficient of RPD than OPD (0.66 vs -0.40, p=0.08, α=0.1). Conclusions: Our study suggests that robotic PD is safe and not inferior to open PD and our analysis RPD demonstrated a higher therapeutic index than OPD. Randomised controlled trials are required to establish the efficacy of robotic PD. Also, standardisation of reporting mortality, survival and oncological outcomes is needed for the effective calculation of TI.